Comparison of use of Information and Communication Technologies between Agricultural Researchers and Extension Personnel in Nigeria - T O Yekinni; L A Akinbile (Journal of Agricultural Extension, 2014)
The study compared the use of ICTs between researchers and extension personnel. Agricultural researchers and extension personnel constituted the study population. Multistage random sampling was adopted to select the respondents. Proportionate random sampling technique was used to select three, two and two of the research stations in the South-West, Central and North-West agricultural zones respectively while the only research stations in each of South-East and North-East zones were selected. Ten percent of the researchers at the selected stations were randomly sampled. Then, 10% of the extension personnel in the 6 state ADPs, where the research stations are located were randomly selected. Structured questionnaire was used to collect information from the respondents. Descriptive and inferential statistics were used to analyse the variables of the study at p=0.05.  Most researchers (75.3%) and few extension personnel (34.1%) had high ICT knowledge score. Mean ICT use score was 33.0±15.8 for researchers and 25.8±15.0 for extension personnel. The log likelihood of researchers’ use of ICTs was significantly reduced by grade level (β=-0.729), increased by access to ICTs (β=1.807) and increased by perception of use of ICTs (β=0.303). The log likelihood of extension personnel’s use was significantly increased by available ICT facilities (β=0.343), access to ICTs (β=1.410), and constraint assessment (β=0.182). The disparity in ICT availability to agricultural researchers and extension personnel presents a serious challenge to agricultural information management in Nigeria. Hence, availability and accessibility were the major determinants of Information and Communication Technologies used by researchers and extension personnel.